1990
DOI: 10.1148/radiology.177.1.2399326
|View full text |Cite
|
Sign up to set email alerts
|

Acute cervical spine trauma: correlation of MR imaging findings with degree of neurologic deficit.

Abstract: A retrospective analysis of magnetic resonance (MR) imaging studies of 78 patients with acute cervical spinal cord injuries was undertaken to determine which observations related directly to the neurologic injury. All MR imaging studies were performed on a 1.5-T unit and assessed with respect to 14 parameters related to the bony spine, ligaments, prevertebral soft tissues, intervertebral disks, and spinal cord. Forty-eight patients also underwent non-contrast material-enhanced thin-section computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(133 citation statements)
references
References 0 publications
9
123
0
1
Order By: Relevance
“…2 ± 7 Except for the Flanders et al 7 study, prior studies are based on small numbers, 2,3,5 or technical descriptions of MR scanners and their accuracy in depicting cord pathology. 3,4 The early studies 2 ± 4 focused on the correlation of MR imaging results with neurological prognosis, and reported that the presence of hemorrhage, edema, or cord compression on MRI was an indicator of poor neurological recovery.…”
Section: Resultsmentioning
confidence: 99%
“…2 ± 7 Except for the Flanders et al 7 study, prior studies are based on small numbers, 2,3,5 or technical descriptions of MR scanners and their accuracy in depicting cord pathology. 3,4 The early studies 2 ± 4 focused on the correlation of MR imaging results with neurological prognosis, and reported that the presence of hemorrhage, edema, or cord compression on MRI was an indicator of poor neurological recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies of prognosis should be undertaken to incorporate new factors such as the DPR and the severity of the damage to the spinal cord by MRI studies. 19 These ®ndings could be used 20 to develop formulas that integrate all of the prognostic factors and take into account the new acute interventions such as improved emergency medical technician (EMT) services and neuroprotective agents. 44 ± 46 The DPR has prognostic signi®cance, when it persists for 48 h or longer in regard to the severity of the injury (ASIA grade) and the potential for ambulation at the time of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this suggestion and reports by ourselves 14 and others 15 of the presence and prognostic signi®cance of a pathological re¯ex known as the delayed plantar response (DPR), which occurs early after spinal cord injury (SCI), it appeared reasonable to examine more thoroughly re¯ex recovery during the immediate period following SCI. In addition, due to the increased emphasis on relating initial neurological ®ndings alone to functional recovery 16 ± 18 or combined with imaging studies 19,20 electrophysiological studies 21,22 and histopathology, 23,24 the following study was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with injuries below the level of the conus medul laris, or with more than one clinical level of impairment, were excluded. The mechan ism of injury was: motor vehicle accident (16), fall (8), diving (3), assault (3) and recreational sport (3). All patients had temporary spinal immobilisation, with 3 undergoing surgical decompression, be tween 6 hours and 12 days from injury.…”
Section: Methodsmentioning
confidence: 99%